Design and Fabrication of Solar Dryer System for Food Preservation of Vegetables or Fruit - Ankit Kumar; Kamred Udham Singh; Mukesh Kumar Singh; Alok Kumar Singh Kushwaha; Abhishek Kumar; Shambhu Mahato (Journal of Food Quality)
Food preservation has been practised in many parts of the world for thousands of years, and it applies to a wide range of foods, including fruits, vegetables, cereals, and meat. Food preservation techniques are canning, freezing, pickling, curing (smoking or salting), and drying. Food spoilage caused by moisture is caused by the growth of mould, yeast, bacteria, and enzymes in the food. The drying process removes enough moisture from food to significantly reduce the humidity level’s likelihood of these adverse outcomes. The material's content measures how much moisture is present in that substance. The moisture content of fresh food can range from 20 to 90 percent depending on the type of food consumed. There will be no signs of moisture in food that has been thoroughly dried before being chopped. We used the experimental analysis in this study to create a mathematical model that could be used to determine which parameter was most important in the design of a solar dryer. In the future, the model is expected to be a helpful design tool for estimating the short- and long-term performance of a solar dryer under load and overload scenarios. The simulation of a solar dryer system has been performed under conditions such as the gap between the glass and the absorber plate, and the impact of hole size. The optimal hole size and spacing between the glass and the absorber plate are determined.